Efektivitas Larva Black Soldier Fly (Maggot) dalam Pengomposan Sampah Dapur dan Pemanfaatannya sebagai Buku Petunjuk Praktikum IPA SMP - Ika Lia Novenda; Rohmah Jwita Sari; Erlia Narulita (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
The problem of waste is increasingly complex, the composition of the largest contributor to waste is organic waste by 60%. Efforts to reduce waste are one of them by composting. Composting organic waste in a natural way takes 3-4 months, thus composting needs to use an effective decomposer to speed up composting, one of which is with the help of Black Soldier Fly (BSF). In addition, knowledge of composting needs to be applied at the education level. This study aims to determine the level of effectiveness of Black Soldier Fly larvae in composting waste and to determine the feasibility of a practical manual compiled from the results of research on the effectiveness of Black Soldier Fly (BSF) larvae. The research method uses experiments. The type of media used was vegetable, fruit and mixed waste, for the larvae used were 10 days old. The results showed that there were significant results, all media showed blackish brown color, humus smell, crumb texture, temperature 26-27Â°C, pH 6.8-7.1, and C/N ratio 2.75-6.81. %, as well as the junior high school science practicum instructions were categorized as very feasible to be used in helping the learning process with an average validity score of 88%.